PROTOTYPING SHARED LIVING: COLLECTIVE RESIDENTIAL EXPERIMENTS - Orlek, Jonathan; Cerulli, Cristina; Parsons, Mark (BDC. Bollettino Del Centro Calza Bini, 2017)
This paper explores opportunities for shared collective domestic experiences, using practice based research, activism and performance art/architecture to develop critical responses and new architectural roles and meanings. Two projects, initiated by Studio Polpo, will be explored: a series of residential performances called OPERA (Open Public Experimental Residential Activity) and a newspaper publication titled “Experimental Residential. How Could Short-Term Shared Living be introduced into UK City Centres?”. How can the making of the home be used to connect the personal, domestic and familial with the collective? This question is central to both of the projects described. In bringing these projects together we hope to develop and articulate alternative architectural practices, which invite collective concerns and desires. Keywords: prototyping, shared living, vacant buildings